199 Subsequent injury risk is not specific to concussion in rugby union. (3rd March 2020) - Moore, Isabel; Vicary, Danielle; Rafferty, Jim; Mathema, Prabhat
Abstract : Background: Subsequent injury risk following concussion has been reported in several sports, with Welsh and English Rugby Union reporting 38 and 60% greater risk respectively. However, other priority injuries have not been examined with similar statistical analysis, yet they may also exhibit the same increase in risk. Objective: The aim of this study was to assess subsequent injury risk following the top four non-concussive injuries in Welsh rugby. Design: Prospective, cohort study. Setting: Professional Rugby Union. Patients (or Participants): Club and National first team players during 2012–13 to 2015–16 seasons. Interventions (or assessment of risk factors): Priority match injuries based on injury incidence were: thigh haematomas, hamstring muscle strains and, ankle and shoulder ligament sprains. The risk of subsequent injury for each specific injury was compared to the risk of subsequent injury after sustaining any other injury using cox proportional hazard ratios. Main outcome measurements: Risk of any injury pre and post the index injury. Results: Thigh haematoma had a greater risk of injury pre- (HR: 1.18, 95%CI: 1.02–1.37, p=0.027) and post-injury (HR: 1.28, 95%CI: 1.13–1.46, p<0.001), and hamstring muscle strains had a greater subsequent injury risk (HR: 1.17, 95%CI: 1.02–1.34, p=0.024) compared to any other injury. Whilst, ankle ligament sprains (HR: 1.25, 95%CI 1.05–1.48, p=0.011) and shoulder ligament injuries (HR: 1.32, 95%CI: 1.11–1.57, p=0.002) demonstrated a greater injury risk pre-injury than prior to any other injury. Conclusions: The findings show that increased subsequent injury risk is not unique to concussion, as it also occurs for hamstring muscle strains. Thigh haematomas have elevated injury risk both before and after its occurrence. However, joint ligament injuries appear to occur to individuals with a high injury risk before sustaining the injury. Further research is warranted to identify risk factors that contribute to these different injury risk profiles.